Determination of 5-aminosalicylic acid in pharmaceutical formulations by square wave voltammetry at pencil graphite electrodes - Uliana, Carolina V. [UNESP]; Yamanaka, Hideko [UNESP]; Garbellini, Gustavo S.; Salazar-Banda, Giancarlo R. (Sociedade Brasileira de Química, 2010)
An analytical method for the determination of the anti-inflammatory drug 5-aminosalicylic acid (5-ASA) in pharmaceutical formulations using square wave voltammetry at pencil graphite electrodes was developed. After the optimization of the experimental conditions, calibration curves were obtained in the linear concentration range from 9.78 × 10-7 to 7.25 × 10-5 mol L-1 resulting in a limit of detection of 2.12 ± 0.05 x 10-8 mol L-1. Statistical tests showed that the concentrations of 5-ASA in commercial tablets and enemas obtained with the proposed voltammetric method agreed with HPLC values at a 95% confidence level.
Keywords: 5-aminosalicylic acid; pharmaceutical formulations; pencil graphite electrode